West Indies : : General, immigration - Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1844)
Colonial Office file containing correspondence and regulations relating to the emigration from India to the West Indies of workers, tender documents for their transport by ship, measures to ensure the safety of 'coolie labour' during the voyage, and the payment of ships' masters